Identification of antiretroviral mutation in protease and reverse trancriptase inhibitor in human immunodeficiency virus-1 of hiv/aids patients in mimika regency, papua - Widiyanti, Mirna; Fitriana, Eva; Natalia, Evi Iriani; Wike, Irawati (Folia Medica Indonesiana, 2017)
Treatment with RT Inhibitors has been used as first line program in Mimika. Regular use of antiretroviral drugs can lower the amount of the virus, but after that HIV can become resistant to the drugs given. Viral resistance to the drugs can occur because of a mutation. If the resistance-associated mutations occur in the DNA of the virus, then the ARV provided will no longer be effective. The aim of this study was to identify the presence of resistance-associated mutations in DNA fragment that encodes the protease and reverse transcriptase. This study used cross sectional design with 84 subjects who had received antiretroviral for > 6 months. The study was conducted in Mitra Masyarakat Mimika Hospital. Laboratory process included extraction, RT-PCR, electrophoresis and sequencing. Data analysis used resistance interpretation algorithms in HIV Database. Results showed that 1 subject who did not receive protease therapy was identified as having minor mutation L10V, 1 subjects receiving NRTI inhibitors had mutation M184V motive and 1 subjects with M41L motive and 1 subjects who received NNRTI inhibitor therapy identified as having mutated Y181C and V108I motive. In conclusion, mutant HIV-1 related to ARV resistance has been identified in two subjects who had received antiretroviral therapy in Mitra Masyarakat Mimika Hospital.